The Halloween effect in European sectors - Carrazedo, T. (2016)
We present economically and statistically empirical evidence that the Halloween effect is significant. A trading strategy based on this anomaly works persistently and outperforms the buy and hold strategy in 8 out of 10 indices in our sample. We present evidence that the Halloween strategy works two out of every three calendar years and if an investor followed it “blindly”, it would yield an annual average excess of return of approximately 2.4%, compared to the buy and hold strategy and further ensure a significant reduction in risk in all indices (around 7.5% on an annual basis). We have considered several possible explanations for the anomaly, however, none was able to fully justify the seasonal effect. We suggest that a possible explanation may be related to negative average returns during the May–October period, rather than superior performance during the November–April period.